2010
DOI: 10.1074/jbc.m110.157214
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid-binding Domain of Wild Type and Mutant α-Synuclein

Abstract: ␣-Synuclein (␣S) is linked to Parkinson disease through its deposition in an amyloid fibril form within Lewy Body deposits, and by the existence of three ␣S point mutations that lead to early onset autosomal dominant Parkinsonism. The normal function of ␣S is thought to be linked to the ability of the protein to bind to the surface of synaptic vesicles. Upon binding to vesicles, ␣S undergoes a structural reorganization from a dynamic and disordered ensemble to a conformation consisting of a long extended helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 75 publications
7
99
0
Order By: Relevance
“…These helices are stabilized by interaction with a variety of phospholipid bilayers, though α-synuclein interacts preferentially with membranes of high curvature and an abundance of acidic phospholipids, properties consistent with those of synaptic vesicles (Davidson et al, 1998; Zhu et al, 2003). Upon interaction with membranes of low curvature α-synuclein adopts a distinct secondary structure characterized by a single extended helix that includes both previously described helical domains and the linker region (amino acids 38–44) (Ferreon et al, 2009; Georgieva et al, 2010; Trexler and Rhoades, 2009). All known mutations associated with familial PD (A30P, E46K, H50Q, G51D, A53E, and A53T) are found in the N-terminal domain (Krüger et al, 2008; Lesage et al, 2013; Pasanen et al, 2014; Polymeropoulos et al, 1997; Proukakis et al, 2013; Zarranz et al, 2004).…”
Section: α-Synuclein Structural Flexibilitymentioning
confidence: 99%
“…These helices are stabilized by interaction with a variety of phospholipid bilayers, though α-synuclein interacts preferentially with membranes of high curvature and an abundance of acidic phospholipids, properties consistent with those of synaptic vesicles (Davidson et al, 1998; Zhu et al, 2003). Upon interaction with membranes of low curvature α-synuclein adopts a distinct secondary structure characterized by a single extended helix that includes both previously described helical domains and the linker region (amino acids 38–44) (Ferreon et al, 2009; Georgieva et al, 2010; Trexler and Rhoades, 2009). All known mutations associated with familial PD (A30P, E46K, H50Q, G51D, A53E, and A53T) are found in the N-terminal domain (Krüger et al, 2008; Lesage et al, 2013; Pasanen et al, 2014; Polymeropoulos et al, 1997; Proukakis et al, 2013; Zarranz et al, 2004).…”
Section: α-Synuclein Structural Flexibilitymentioning
confidence: 99%
“…Experiments have identified two predominant states for monomeric α S bound to anionic membranes, a horseshoe-like broken helix identified with NMR and EPR (Ulmer et al, 2005; Drescher et al, 2008; Rao et al, 2010) where a kink brings together the two helical segments, and an extended kink-free helix conformation without a kink postulated by ESR and DEER experiments (Jao et al, 2004; Georgieva et al, 2008; Jao et al, 2008; Trexler and Rhoades, 2009). It has been suggested that the extended and broken-helix conformations could interconvert (Georgieva et al, 2010; Robotta et al, 2011; Lokappa and Ulmer, 2011), potentially in a lipid-dependent fashion (Borbat et al, 2006; Middleton and Rhoades, 2010). Outside of coarse-grained simulations (Braun et al, 2012; Braun and Sachs, 2015), this conformational diversity had not been sampled, and presented a prime candidate for using the HMMM model to investigate the specific lipid interactions that determine the membrane-bound structure of α S.…”
Section: Applications Of Hmmm To Membrane-associated Phenomenamentioning
confidence: 99%
“…1A). The protein adopts a predominantly broken or continuous α-helical structure upon binding high- or low-curvature membranes, respectively (Chandra et al, 2003; Ferreon et al, 2009; Georgieva et al, 2010; Trexler and Rhoades, 2009; Ulmer et al, 2005). Interactions involving an N-terminal segment spanning residues 1–25 are critical for membrane binding and for the adoption of an α-helical structure (Bartels et al, 2010).…”
Section: Introductionmentioning
confidence: 99%